PEMANFAATAN TEPUNG MANURE HASIL DEGRADASI LARVA LALAT HITAM (Hermetia Illucens L) TERHADAP PERFORMANS AYAM KAMPUNG FASE LAYER - Nangoy, Monalisa M.; Montong, Martina E.R.; Utiah, Wapsiaty; Regar, Mursye N. (ZOOTEC, 2017)
UTILIZATION OF MANURE DEGRADED BY BLACKFLIES LARVAE (HERMETIA ILLUCENS L) ON THE PERFORMANCE OF LAYING NATIVE CHICKEN. Native chicken is one of the livestocks that have been widely used for source of protein. It has already been maintained everywhere in Indonesia. Native chickens is widely kept for eggs because it contains good nutrients for human beings. One of the source of rations for native chicken is manure flour from the degradation of the blackflies larvae (MHD flour). This feed material contains a good nutritional value for this chicken. In this study the results of the degradation of manure blackflies larvae processed into flour and added into the rations with the aim to know the consumption of rations, egg production and rations conversion of native chicken. 40 native chickens females aged 56 weeks had been used.Baterry system cages of 50x50x75 cm in size was used to kept the native chickes. Placement of chicken in each unit was done randomly. A randomized complete design (RAL) with 4 treatment and 5 replications was used as design methods (Steel and Torrie, 1991). Each replication using native chickens age 56 weeks with the following treatments: R0 = 0% flour MHD: R1 = 5% flour MHD: R2 = 10% flour MHD: R3 = 15% flour MHD. The variable measured is the sum of rations consumption, egg production and rations conversion. The results obtained showed that there was highly significant difference (P < 0.01)between treatmentsandrations consumption, egg production, and there was no significant difference (P > 0.05) between treatmens and rations conversion. It can be concluded that as much as 15% of the MHDcan be used in chicken rations. Keywords: Native Chicken, Black Flies, MHD flour.